PENGARUH BEBAN KERJA, STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KELELAHAN KERJA PADA PEGAWAI DIVISI PRODUKSI PT SUPER TEKNIK BSD SERPONG KABUPATEN TANGERANG - Hani Annisa (2022)
This study is a quantitative research that aims to determine and prove the effect of workload, work stress, and work environment on burnout. This study used all employees of the production division at PT Super Teknik BSD Serpong Tangerang Regency as a sample with a total of 60 employees which was carried out using probability sampling technique. The analysis technique applied in this study is descriptive analysis technique and inferential analysis with the help of the SmartPLS 3.0 test tool. While the hypothesis is t test with a significance level of 5% (0.05). The results of this study indicate (1) workload has a positive and significant effect on burnout, (2) work stress has a positive and significant effect on burnout, (3) work environment has a positive and significant effect on burnout, and (4) Workload, work stress, and work environment simultaneously affect burnout. Keywords: human resources, workload, work stress, work environment, and Burnout.